Attitude, Knowledge, Motivasi, Skill dan Pengaruhnya Terhadap Kinerja Karyawan : (Studi pada Karyawan di PT. Titan Teknikatama Indonesia) - Kadarisman Kadarisman; Agus Purbo Widodo; Heri Sudarsono (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study was to determine the effect of attitude, knowledge, motivation and skill simultaneously and partially on Employee Performance. This study was conducted at PT Titan Teknikatama Indonesia Jakarta, involving 75 respondents taken based on random sampling techniques. The research approach used a quantitative method that included research instrument testing, descriptive statistical analysis, multiple linear analysis, classical assumption testing, and hypothesis testing. The results showed that Attitude had a positive and significant effect on Employee Performance. Knowledge had a positive and significant effect on Employee Performance. Motivation had a positive and significant effect on Employee Performance. Skill had a positive and significant effect on Employee Performance. Attitude, knowledge, motivation and skill had a positive and significant simultaneous effect on Employee Performance. Among the independent variables, attitude has the largest contribution to Employee Performance.